Domestic Conflicts in Modern Russia through the Prism of Jokes - Anastasiya Yu. Khromacheva (Социологическая наука и социальная практика, 2016)
The image of a modern family is very relevant today, since creating an archetype of society as a whole, as well as of its specific aspects, always leaves an imprint on the people’s subconscious, prompting them to recreate certain behavioral patterns. Undoubtedly, even when the archetype being imprinted is completely positive, it is not always possible to reproduce the desired and socially acceptable pattern, since this requires certain material resources, a fitting mental state, and emotional motivation. But even so, the mass culture continues to generate a very specific image of the modern family, which is not as much a desired archetype (like, for instance, the families shown in commercials) as a reflection of the transformation that family undergoes as an entity. This article reviews the results of the content analysis of folkloric texts, namely jokes about the modern Russian family. We have selected 600 samples of text, which contain the most complete descriptions of the typical relations within the family and the main forms and types there of. These jokes have been analyzed from the point of view of domestic conflicts. We have classified conflict-themed jokes in terms of conflict types and interactions between family members. The main conclusion is that conflicts in the modern Russian family mostly stem from the lack of economic resources, which is mostly typical of young families, as well as from profound psychological tension.